(untitled) (Global Journal of Medical Research, 2016)
The electrochemical detection of staphylococcus aureus by the electrode of clay paste modified by amoxicillin (AMX-Clay) is described. The electrodes of AMX-Clay were then used to detect the staphylococcus aureus with low optical densities by using the cyclic voltammetry (CV), the voltammetry with square waves (swv) and the spectroscopy of electrochemical impedance (EIS) in physiological mediums. Electrochemical parameters like the time of deposit and the concentration of the amoxicillin on the surface of the clay electrode were optimized. The elaborate electrode showed a good electroactivity, resulting in the packing of current, in the presence of the bacteria.